Intrathoracic anastomosis using handsewn purse-string suturing by the double-ligation method in laparo-thoracoscopic esophagectomy - Takamasa Takahashi; Yuji Kaneoka; Atsuyuki Maeda; Yuichi Takayama; Hiroki Aoyama; Takahiro Hosoi; Kazuaki Seita (Journal of Minimally Invasive Surgery)
Purpose: In minimally invasive esophagectomy (MIE), it is important to reduce the rate of anastomotic leakage to ensure its safety. At our institute, the double-ligation method (DLM) has been introduced to insert and fix the anvil of the circular stapler for intracorporeal circular esophagojejunostomy in gastric surgery. We adopted this method for intrathoracic anastomosis (IA) in MIE. The aim of this study was to investigate the safety of IA with DLM in MIE. Methods : In this study, 48 patients diagnosed with primary middle or lower third segment thoracic esophageal carcinoma with clinical stage I, II, III or IV disease were retrospectively evaluated. Postoperative outcomes were assessed. Results : Among the 48 patients, 42 patients underwent laparo-thoracoscopic esophagectomy and IA using a circular stapler with the DLM. The average total operation time and thoracoscopic operation time were 433 and 229 minutes, respectively. The average purse-string suturing time was 4.7 minutes. The rates of anastomotic leakage and stenosis were 2.4% and 14.3%, respectively. The overall incidence of postoperative complications (Clavien-Dindo grade of ≥III) was 16.7%. The average postoperative stay was 16 days. Conclusion : The procedure of IA using a circular stapler with the DLM in MIE was safe and provided a low rate of anastomotic leakage.